Microscopic observations and interpretations of the progressive fracture in Kuru granite under uniaxial compression. Issue 1 (August 2021) - Wan, W; Li, C C
Abstract: Kuru granite is strong and brittle so that it is prone to strain burst. A series of laboratory tests were carried out to investigate the fracturing process in both pre- and post-peak stages under uniaxial compression. The progressive fracturing in the cylindrical specimens was monitored by acoustic emission (AE) technique. The specimens were loaded to different levels both in pre-peak and post-peak stages. After that, the load was removed and two thin sections, one parallel and the other perpendicular to the loading direction, were prepared from each specimen. The fractures in the specimens were microscopically observed. The geometry of each fracture was quantified by its length, opening and orientation. The results show that noticeable fracture propagation occurs mainly at the stress level above 80% of the Uniaxial Compressive Strength (UCS). In general, intergranular cracks dominate in the whole loading process, but after the peak stress the density of intragranular cracks becomes comparable to the intergranular cracks. The percentage of the intergranular first rises and then drops with an increase in the damage of the material. The variation in the number of intragranular cracks is opposite. The intergranular cracks dominate in the beginning of fracture initiation and during the stage of stable fracture propagation, but the intragranular cracks begin to flourish during the stage of unstable fracture propagation. The propagation of intragranular cracks consumes more energy than intergranular cracks. The fracture propagation in the loading direction becomes dominant with an increase in the damage of the rock and finally the specimen fails in splitting. The microscopic observations reveal the fracturing pattern of the burst-prone rock, which are useful data for the study of the physics of strain burst in rock.